Actin-Binding Proteins in Nerve Cell Growth Cones - Ryoki Ishikawa; Kazuhiro Kohama (Elsevier, 2007)
The motility of the growth cone, an intracellular apparatus located at the tip of the axon in developing neurons, is thought to govern axonal path-finding and the construction of neuronal networks. Growth cones contain an actin-rich cytoskeleton, and their dynamics are regulated by a wide variety of actin-binding proteins and motor proteins. In this review, we will focus on the principal functions of these proteins, their mutual interactions in vitro, and their possible roles in the dynamics of nerve cell growth cones. Keywords:: actin, myosin, actin-binding protein, growth cone dynamics, neurite elongation